(untitled) (Turkish Journal of Computer and Mathematics Education (TURCOMAT), 2021)
The purposes of this research were 1) to study the characteristics of competency of Sangha administrators in Surin province, 2) to study the competency and competency indicators of Sangha administrators in Surin province, and 3) to study the competency development and competency indicators of Sangha administrators in Surin province. This research is qualitative. Documentary study and in-depth interview with 10 key informants that’s a good prototype and selected purport sampling, were used. Qualitative information by classifying and organizing information. The data were analyzed by using descriptive. The results had found that: - the characteristics of competency of Sangha administrators in Surin province found that administration aspect is meetings, work planning, project preparation, etc. The religious studies aspect is an educational organization, supporting the management of education inside and outside the temple. Study welfare’s aspect is learning centers, which are set up within the temple and encouraging education for children etc. The Buddhist propagational aspect is moral and ethical training for a person and organized important Buddhist day activities etc. The public welfare aspect is the construction of buildings, lodgings for monks, etc. Finally, the public welfare aspect is assistance for the victims, Financial support for the construction of hospitals and priest hospital buildings, etc. 2) The competency of Sangha administrators consists of 9 competencies are:- 1) general competency consisted of 3 three competencies namely: (1) morality, (2) good communication, and (3) being a good model manner, 2) self-competency consisted of 3 sub-competencies are (1) teamwork, (2) helping others, and (3) trusting, and in each sub-competency is consisted of 3 three components are knowledge, skill, and attitude. 3) The Development of performance and performance indicators of sangha in Surin Province The performance of the sangha in Surin province has been developed appropriately. Includes (1) General performance, there are three indicators: (1) morality, ethics, (2) good communication, and (3) a good example, (2) self-performance, 3 indicators, (1) self-leadership, (2) intelligence development, and (3) Performance with others 3 indicators: (1) teamwork, (2) helping others, (3) trustworthy